O custo da doença: revisão de literatura The costs of disease: review of the literature - José Duarte de Araújo (Universidade de São Paulo, 1975)
Foi feita revisão da literatura, internacional e nacional, sobre o custo da doença e suas repercussões econômicas na população. A review of national and international literature on the costs of disease and its economical consequences on the population was performed.